(3HMQ GdCfSGHs - (3CHh eMeO, Qcf GdOjf, GdMSf GdMSjfj GdehUdjs
(3ChdgG (B:s
(3GdMeO ddg (B.... (3GdPj fhQ bdhH ChdjGFg HeUGHjM GdeYGQa hUhQ CdhGM aXfJge CSQGQ GdYdhe (B... (3hhgHge Yjf Gdjbjf eG QhGge ef eGA GdYhGQa hJLdi dge GdXGgQ hGdHGWf (B...s
(3BNQgG (B:s
.. (3hbjd Cda hKdKeGFI SfI , gPg GdJQLeI fbdJgG ef cJGH JGQjN eQBJ GdReGf JCdja GdTjN GdaGVd GdSHW GHf GdLhRj Ydjg GdQMeI hGdMeO ddg hMOgs
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3GdJedcGJ h GdhbajGJ (B:s
(3Jedc (B: (3eMeO egOj eMeO MSf GdehShj GdNQSGfj , SfI (B: 20 (3ThGd (B1405 (3g`s
Keywords: (3GdJGQjNs